Análise preditiva de emplacamentos de implementos rodoviários usando modelos de séries temporais e redes neurais : estudo de caso comdados da ANFIR(2013-2024) - Dondé, Maicol Mauricio Souza (My University, 2025)
This study proposed the development of a predictive model for the registration of road implements in Brazil, based on historical data provided by ANFIR for the period from 2013 to 2024. The research adopted a hybrid approach, combining traditional statistical time series techniques such as ARIMA and SARIMA with contemporary machine learning and artificial intelligence methods, including Artificial Neural Networks (ANN), Deep Learning, Naive Bayes, Random Forest, Multiple Linear Regression (MLR), Simple Linear Regression (SLR), Exponential Smoothing, and XGBoost. The primary objective was to identify seasonal patterns, historical trends, and nonlinear relationships among multiple variables that influence the behavior of the implement market.The analysis was conducted using historical registration data for Trailers/Semi-trailers and Truck Bodies, with an initial assessment covering the full period from 2013 to 2023. This segmentation enabled a comprehensive understanding of registration trends, taking into account key economic events such as the 2014-2016 recession, marked by GDP contractions of -3.5% and -3.3% (according to IBGE), and the COVID-19 pandemic in 2020, which severely affected production and sales in the sector. Due to these disruptive events, the data were further segmented into two additional timeframes: from 2018 to 2023, to capture more recent trends, and from 2021 to 2023, to isolate the effects of the pandemic.The forecasts generated by each model were compared to the actual 2024 data using evaluation metrics such as Mean Absolute Percentage Error (MAPE), Mean Absolute Error (MAE), and Root Mean Squared Error (RMSE). In the full period analysis (2013-2023), the SLR model stood out as the most effective for predicting semi-trailer registrations, achieving strong performance metrics (MAPE = 5.93%; MAE = 437.33; RMSE = 494.60), proving particularly effective in contexts with regular seasonality. Exponential Smoothing also performed well (MAPE = 6.57%) by leveraging the linear trend in the historical data. In the post-pandemic period (2021-2023), SLR again emerged as the best-performing model (MAPE = 5.21%; MAE = 370.30; RMSE = 472.55), reflecting the predominance of a linear trend during this shorter interval. The Deep Learning model also delivered satisfactory results (MAPE = 5.36%), though its higher computational cost limits practical applicability. Based on these results, it is recommended to use the SLR model for long-term forecastsof semitrailer registrations, complemented by Exponential Smoothing to capture specific seasonal effects. For more recent periods, SLR is suggested when a clear linear trend is present; otherwise, Deep Learning demonstrates greater effectiveness. In the case of truck bodies, models such as ARIMA (2013-2023, MAPE = 14.96%), MLR (2018-2023, MAPE = 9.37%), and Deep Learning (2021-2023, MAPE = 13.75%) proved to be better suited to the variability in the data for those specific timeframes. Finally, the importance of continuous monitoring and periodic recalibration of the models is emphasized, as unexpected events-such as economic crises or pandemics-can significantly alter historical patterns and compromise predictive accuracy. [resumo fornecido pelo autor]
Esta dissertação propôs o desenvolvimento de um modelo preditivo para os emplacamentos de implementos rodoviários no Brasil, com base em dados históricos disponibilizados pela ANFIR, no período de 2013 a 2024. A pesquisa adotou uma abordagem híbrida, combinando técnicas estatísticas tradicionais de séries temporais, como ARIMA e SARIMA, com métodos contemporâneos de aprendizado de máquina e inteligência artificial, incluindo Redes Neurais Artificiais (RNA), Deep Learning, Naive Bayes, Random Forest, Regressão Linear Múltipla (RLM), Regressão Linear Simples (RLS), Suavização Exponencial e XGBoost. O principal objetivo foi identificar padrões sazonais, tendências históricas e relações não lineares entre múltiplas variáveis que influenciam o comportamento do mercado de implementos. A análise foi conduzida com base em séries históricas de emplacamentos de Reboques/Semirreboques e Carrocerias Sobre Chassis, com uma avaliação inicial do período completo de 2013 a 2023. Essa primeira segmentação permitiu uma compreensão abrangente da evolução dos emplacamentos, considerando eventos econômicos relevantes como a recessão de 2014-2016, marcada por retrações do PIB de -3,5% e -3,3% (IBGE), e a pandemia da COVID-19 em 2020, que afetou diretamente a produção e as vendas do setor. Diante desses eventos disruptivos, os dados foram segmentados adicionalmente em dois recortes: de 2018 a 2023, visando capturar tendências recentes, e de 2021 a 2023, para isolar os efeitos da pandemia. As previsões geradas pelos modelos foram comparadas aos dados reais de 2024, utilizando métricas como Erro Percentual Absoluto Médio (MAPE), Erro Absoluto Médio (MAE) e Raiz do Erro Quadrático Médio (RMSE). No recorte completo (2013-2023), o modelo RLS destacou-se na previsão de semirreboques (MAPE = 5,93%; MAE = 437,33; RMSE = 494,60), sendo eficaz em contextos com sazonalidade regular. Em seguida, a Suavização Exponencial também teve bom desempenho (MAPE = 6,57%), aproveitando tendências lineares nos dados. No período pós-pandemia (2021-2023), a RLS novamente se mostrou superior (MAPE = 5,21%; MAE =370,30; RMSE = 472,55), refletindo a dominância de uma tendência linear. O modelo Deep Learning também teve desempenho satisfatório (MAPE = 5,36%), embora seu alto custo computacional limite a aplicabilidade prática. Com base nesses resultados, recomenda-se o uso da RLS para previsões de longo prazo de semirreboques, com apoio da Suavização Exponencial para capturar variações sazonais. Para períodos mais recentes, sugere-se a RLS se houver tendência linear; caso contrário, o modelo Deep Learning se mostrou mais eficaz. No caso de carrocerias sobre chassis, modelos como ARIMA (2013-2023, MAPE = 14,96%), RLM (2018-2023, MAPE = 9,37%) e Deep Learning (2021-2023, MAPE = 13,75%) apresentaram melhor adequação à variabilidade desses dados. Por fim, destaca-se a importância do monitoramento contínuo e da recalibração periódica dos modelos, uma vez que eventos inesperados, como crises econômicas ou pandemias, podem alterar significativamente os padrões históricos e comprometer a precisão preditiva.[resumo fornecido pelo autor]
Keywords: Engenharia mecânica; Redes neurais (Computação); Aprendizado do computador; Modelo auto-regressivo integrado de médias móveis; Aprendizado profundo (Aprendizado do computador); Mechanical engineering; Neural networks (Computer science); Machine learning; Box-Jenkins forecasting; Deep learning (Machine learning)